Taking the LEAP : the methods and tools of the Linked Engineering and Manufacturing Platform (LEAP) - Kiritsis, Dimitris (Academic Press is an imprint of Elsevier, 2016)
Taking the LEAP: The Methods and Tools of the Linked Engineering and Manufacturing Platform (LEAP) shows how to use the LEAP methodology to organize all product lifecycle information needed to drive engineering and manufacturing processes, and also provides knowledge exploitation solutions to support design decisions. This book not only explains in detail what LEAP is and how to use it, but also provides LEAP case studies from sectors such as auto manufacturing and offshore engineering. The intensity of competition in the global manufacturing industry has increased dramatically in the past decade, presenting challenges and opportunities to new operators and traditional centers alike. Using the latest ICT developments effectively is increasingly important in order to meet demands for mass customization, sustainability, and improved productivity. To achieve these goals, the Linked Engineering and manufacturing Platform (LEAP) was developed as an integrated information system for manufacturing design.